Multi-visceral resection in colonic cancer - “Boon or Bane?”: exploring the role and rationale through case reports - Shanmugam, Subbiah; Thirunavukkarasu, Suganthan (International Surgery Journal, 2024)
Colonic cancer invading into the adjacent organs or structures is detected in 5% to 20% of all surgical interventions performed for the management of colonic cancer. These adhesions may be either due to frank tumor infiltration or due to peritumoral inflammation. Nature of these adhesions cannot be ascertained intraoperatively. Standard management entails in block resection of the diseased organ along with adjacent organ infiltration. The release of macroscopically infiltrated tissue is not recommended due to the risk of perforation, tumor seeding and the possibility of leaving residual disease (R1, R2) with high recurrence rates. We share our experience with two case reports regarding the role of multi-visceral resection in clinically diagnosed locally advanced colonic cancers adherent to adjacent structures but pathologically down staged and proved to be inflammatory adhesions and desmoplastic reaction. In both patients even adjuvant therapy was not needed. Multi visceral resection in carcinoma colon has better prognosis and overall survival, if the histopathology reveals inflammatory adhesions or desmoplastic reaction rather than direct tumor infiltration into adjacent structures. So upfront surgery may be beneficial particularly in patients where the adjacent organ involvement is really not the involvement by tumor.